2012
DOI: 10.1021/jf203073a
|View full text |Cite
|
Sign up to set email alerts
|

Increasing and Stabilizing β-Sheet Structure of Maize Zein Causes Improvement in Its Rheological Properties

Abstract: Wheat gluten proteins are considered to have the unique ability to form viscoelastic matrices that are essential for breadmaking. This study shows that maize seed storage protein (zein), if properly treated, can be made to function similarly to gluten at the protein secondary structure level with concomitant improved viscoelasticity. Here, we propose the concept of a small amount of coprotein (high molecular weight glutenin or casein) acting to stabilize a build-up of β-sheet structure in a zein-based dough, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 16 publications
2
36
0
1
Order By: Relevance
“…The change in zein dough rheology with oxidation by hydrogen peroxide is far less temperature dependant than that found using dilute organic acid treatment and does not require addition of hydrocolloids (Schober et al, 2008) or of co-proteins (Mejia et al, 2012). Although many challenges still remain, oxidative modification of zein rheological properties represents a further step forward in development of technology to enable zein to replace gluten in dough systems.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The change in zein dough rheology with oxidation by hydrogen peroxide is far less temperature dependant than that found using dilute organic acid treatment and does not require addition of hydrocolloids (Schober et al, 2008) or of co-proteins (Mejia et al, 2012). Although many challenges still remain, oxidative modification of zein rheological properties represents a further step forward in development of technology to enable zein to replace gluten in dough systems.…”
Section: Discussionmentioning
confidence: 96%
“…Commercial type zein (essentially α-zein) can form a viscoelastic dough in an aqueous system at 35 o C and higher (Lawton, 1992;Schober et al, 2008Schober et al, , 2010, above its hydrated glass transition temperature (T g ). Several different ways have been investigated to improve the dough rheological properties of zein, including addition of hydrocolloids (Schober et al, 2008) and co-proteins (Mejia et al, 2012). Some hydrocolloids, for example hydroxypropyl methylcellulose, have also been shown to improve gas cell stability in zein breads (Schober et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At Purdue University, researchers pursued the hypothesis that the maize endosperm proteins are simply missing additional elastic HMW-GS that is in wheat, and that addition of a minor amount of this or another similar protein would confer viscoelasticity to the mixture. Mejia et al (2012) showed that addition of such a co-protein, namely HMW-GS or casein (as a non-wheat protein), stabilized the viscoelasticity of the hydrated, heated (to 35 o C), and mixed maize zein, as well as held stable the β-sheet content after mixing had stopped. Furthermore, they hypothesized that both zein and gliadin are affected both in structure and function by their respective co-proteins.…”
Section: Comparison Of Wheat Gluten and Maize Zeinmentioning
confidence: 99%
“…15 Thus, the viscoelastic properties and relaxation rate of the zein polymers appear to be related to stable β-sheet structures.…”
Section: Introductionmentioning
confidence: 99%